PECULIARITIES OF INTERACTION BETWEEN LAW ENFORCEMENT AGENCIES IN SOLVING THE INVESTIGATION OF ILLICIT TRAFFICKING IN NARCOTIC DRUGS AND PSYCHOTROPIC SUBSTANCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article analyzes the interaction of law enforcement agencies in uncovering the investigation of illicit trafficking in narcotic drugs and psychotropic substances and examines the features of tactical methods of interaction when conducting operational search activities and investigative actions.